Uso de los recursos bibliográficos físicos y contrastar con información en el área de ciencias sociales. - Marcillo Cajamarca, María Graciela (2025)
The purpose of this master's thesis, entitled "Use of physical bibliographic resources and contrast with information in the area of social sciences", was to contrast the use of physical bibliographic resources with digital ones, evaluating the quality of information in the context of the Social Studies subject. The general objective was to analyze how students use these resources and what is the perception of teachers and students regarding their accessibility, usefulness and relevance. A quantitative approach methodology was used, using surveys for students, where data on the use and quality of resources was obtained. The results indicated a preference for digital resources, although gaps were identified in the updating and accessibility of physical resources, which affects the learning process. Based on the findings, it is concluded that an improvement in the updating of physical materials and the training of teachers and students in the use of educational technologies could increase the effectiveness of learning in the subject. This modernization proposal sought to strengthen bibliographic resources in the institution, promoting equitable access and improving the quality of teaching.